APPROACH OF SIX SIGMA METHOD TO CONTROL THE QUALITY OF WET MIX PRODUCTS IN THE CREAM MAKING PROCESS - Koesdijati, Titik; Nurcahyanie, Yunia Dwie (UNIPA PRESS, 2019)
One of the process making a creamer is the process of mixing liquid glucose, oil, emulsion powder and water that produces liquid creamer (wet mix / liquid mix). The wet mix results often not match with the standard which can affect the results in the next process. This is the purpose of company to make improvements in controlling wet mix in order to decrease the number of wet mix failure produced. The method used in this research was DMAIC (Define, Measure, Analyze, Improve, Control). Previous data processing was using Seven Tools, with 3 of 7 tools which are the observation sheet (check sheet), pareto diagram, and fishbone diagram. Through data processing and analysis using DMAIC obtained 3 types of failure of semi-finished products (wet mix) which was wet mix as much as 38.8889%, wet mix gross as much as 36.1111%, and wet mix browning 25,0000% and obtained sigma value at Level 3.87. Define is the stage of defining quality problems, and defined the cause. Measure is the stage of measuring the failure rate of the product. Analyze is the stage of quality improvement by analyzing factors causing product failure. Improve is an action plan to improve quality by eliminating factors causing product failure. Control is the last stage of the Six Sigma project that emphasizes the documentation and dissemination of actions that have been done.